LEXICAL STORAGE IN TOURISM STUDENTS OF VOCATIONAL EDUCATION PROGRAM UNIVERSITAS BRAWIJAYA (Word Association Test Case Study) - FIDAYANTI, FIRDIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Lexical item is a fundamental part for language learners in masteringlanguage comprehensively. All of information related to the lexical items is organizedwell in mental lexicon including how the way they store and associate some certainwords. This study aims to investigate lexical storage in tourism students of vocationalprogram. This study uses qualitative method which is applied in case study becausethis study investigates about lexical storage on a group of students. The data of thisstudy are the responses of the participants from word association test’s questionnaire.This study reveals that there are three types of word associations which are produced,namely; syntagmatic association, paradigmatic association, and encyclopaedicassociation. The most dominant responses produced by the participants in thisresearch belong to syntagmatic association (85 responses/ 48%). The second dominantresponse is encyclopaedic association (65 responses/ 37, 71%) and the least responsebelongs to paradigmatic association (25 responses/ 17%). The emergence ofsyntagmatic association as the most dominant response in this study shows that instoring words, the participants actually do not store certain words as a single item, butthey relate them to the words that mostly occur together. Key words : Lexical Storage, Word Association Test, Word Association Types